2015
DOI: 10.1113/jp270570
|View full text |Cite
|
Sign up to set email alerts
|

Post‐exercise cold water immersion attenuates acute anabolic signalling and long‐term adaptations in muscle to strength training

Abstract: Key pointsr Cold water immersion is a popular strategy to recover from exercise. However, whether regular cold water immersion influences muscle adaptations to strength training is not well understood.r We compared the effects of cold water immersion and active recovery on changes in muscle mass and strength after 12 weeks of strength training. We also examined the effects of these two treatments on hypertrophy signalling pathways and satellite cell activity in skeletal muscle after acute strength exercise.r C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
267
4
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(292 citation statements)
references
References 41 publications
16
267
4
5
Order By: Relevance
“…Interestingly, Roberts and colleagues 30 recently assessed both the short-term anabolic signalling and long-term adaptations in muscle to strength training with CWI or an active recovery. It was reported that CWI blunted the activation of key proteins and satellite cells (which regulate hypertrophy) in skeletal muscle up to two days after strength exercise, and also attenuated long-term gains in muscle mass and strength compared to an active recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Roberts and colleagues 30 recently assessed both the short-term anabolic signalling and long-term adaptations in muscle to strength training with CWI or an active recovery. It was reported that CWI blunted the activation of key proteins and satellite cells (which regulate hypertrophy) in skeletal muscle up to two days after strength exercise, and also attenuated long-term gains in muscle mass and strength compared to an active recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Semelhante à outras intervenções, [23][24][25][26][27][28][29][30] o presente estudo também verificou que a IAF não influenciou nenhum parâmetro estudado (CQ, KGST e parâmetros isocinéticos). Allan e Mawhinney 28 descreveram que embora a IAF seja muito utilizada no meio esportivo com a premissa de favorecer a recuperação do atleta, essa alternativa ainda carece de comprovação científica.…”
Section: Discussionunclassified
“…However, recent evidence has shown that acute 10 min of cold water immersion immediately following one resistance exercise session did not have any antiinflammatory benefits for skeletal muscle over the following 48 h post-exercise recovery period [4]. In the longer term, another study showed that 10 min of cold water immersion immediately following every resistance exercise session that was performed twice per week for 12 weeks resulted in diminished gains in muscle strength and muscle hypertrophy [5]. Thus, recent evidence is accumulating against the use of skeletal muscle cryotherapy as a post-exercise recovery intervention.…”
mentioning
confidence: 99%